BILINGUALISM AS A PROMISING FORM IN CHILDREN’S EDUCATION - Tursunboyeva, Mukhlisa (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
The given article is focused on the bilingual education of children and its peculiarity. There’s also highlighted the scientists that carried out a research on this issue and the result of their scientific works.